On lexicalized valency and the valency of (new) complex verbal formations in Slovenian - Žele, Andreja (Slovenski jezik, 2013)
The paper considers the matter of so-called lexicalized valency within the framework of new complex verbal formations in Slovenian, and in consequence, the increasingly dominant ac cusative valency in the language, which can also indicate that the extension of semantic verbal independence simplifies the syntax
Keywords: glagolske tvorjenke; leksikalizirana valenca; lexicalized valency; Slovene; Slovene language; slovenščina; valenca; valency; verbal formations